Assessing the impact of diverse mask types on COPD patients: a randomised controlled trial study protocol - Chen, Xuwen; Jiang, Xiaomei; Zhang, Xuhui; Ren, Dong; Wei, Caihong; Xu, Aihong; Yang, Hong; Bai, Ruijia; Li, Caiyun; Yue, Feiyan; Bao, Shisan; Shi, Jungang; et al. (BMJ open, 2024)
IntroductionWearing masks has proven beneficial in preventing respiratory pathogen infections in individuals with chronic obstructive pulmonary disease (COPD). However, the impact of different mask types on physiological indicators and daily physical activity in COPD patients remains uncertain. This study aims to assess the immediate effects of various mask types on cardiopulmonary function indicators, subjective perceptions and the 6-minute walking distance (6MWD) in individuals with COPD.Methods and analysisThis randomised controlled trial will enrol 129 stable COPD patients. Participants will be randomly divided into three groups: control, N95 mask and surgical mask groups. Each group will undergo both a 6-minute seated test and a 6-minute walk test (6MWT), without or with their respective masks. A 10-minute interval will be provided between the two phases. The primary indicators of the study include the 6MWD and blood oxygen saturation. Secondary outcomes encompass blood pressure, pulse rate, Borg score, Rate of Perceived Exertion (RPE) score and subjective perception score. Oxygen saturation, pulse rate and blood pressure will be recorded four times during the trial, while Borg and RPE scores will be compared before and after the 6MWT. Additionally, subjective perception scores will be collected after each mask-wearing stage.Ethics and disseminationThis study has received approval from the Ethics Committee of the Affiliated Hospital of Gansu University of Chinese Medicine (approval number: 202335). We plan to disseminate research results through publication in a peer-reviewed journal or presentation at a conference.Trial registration numberChiCTR2300074554.